(untitled) (Swiss Medical Weekly, 2025)
A recent hypothesis states that Menière’s disease is caused by inappropriate expression, i.e. enhanced release of the neurotransmitter calcitonin gene-related peptide. Here, we tested this hypothesis by administering rimegepant, a new calcitonin gene-related peptide antagonist approved for the acute treatment of migraine and for the prevention of episodic migraine, to six patients with both Menière’s disease and migraine. Two patients received the first dose of 75 mg rimegepant to treat an acute attack of Menière’s disease. One of these two plus the remaining four patients were treated with 75 mg rimegepant every other day for secondary prevention. One patient developed an allergic reaction after the first administration and was excluded from further treatment. In the two patients treated during acute Menière’s disease, symptoms were relieved and resolved about 30 min earlier than migraine symptoms. While all five patients had reduced migraine, all completely resolved Menière’s symptoms on preventive therapy with rimegepant for up to eight months. These results support the idea that calcitonin gene-related peptide is linked to the pathogenesis of Menière’s disease and suggest that inhibition of calcitonin gene-related peptide signalling may represent a promising therapeutic option for Menière’s disease patients.